2004
DOI: 10.1128/aac.48.8.2883-2887.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amoxicillin Use on Oral Microbiota in Young Children

Abstract: Dental plaque samples from 40 children were screened for the presence of bacteria resistant to amoxicillin. Fifteen children had used amoxicillin and 25 had not used any antibiotic in the 3 months prior to sample collection. All (100%) of the children harbored amoxicillin-resistant oral bacteria. The median percentage of the total cultivable oral microbiota resistant to amoxicillin was 2.4% (range, 0.1 to 14.3%) in children without amoxicillin use and 10.9% (range, 0.8 to 97.3%) in children with amoxicillin us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…Previous studies have shown a correlation between antibiotic use and the emergence of antibiotic-resistant oral bacteria [1][2][3][4][5]. However, other factors have the potential to promote the spread and emergence of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown a correlation between antibiotic use and the emergence of antibiotic-resistant oral bacteria [1][2][3][4][5]. However, other factors have the potential to promote the spread and emergence of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 98%
“…3 Children receive a lot of primary healthcare services and, as such, receive a disproportionately high number of antibiotics compared with middle aged populations. 4 Children are also key drivers of infection within communities and can contribute to the spread of bacteria from person to person. Despite this, little research has been published describing the prevalence of bacterial…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Unfortunately, there is a tendency among veterinarians to use antibiotics as part of the management of any animal with periodontal disease or other oral condition. Resistance of plaque bacteria to antibiotics has clearly been demonstrated in humans, [40][41][42][43] and a similar pattern of bacterial resistance development may be present in cats and dogs.…”
Section: Introductionmentioning
confidence: 88%